Missed opportunities for observation‐based ecology in the Next Generation Science Standards. Issue 4 (11th February 2020) - Merritt, Eileen G.; Bowers, Nicole
Abstract: Observation‐based ecology (OBE) generates critical knowledge about the health of ecological systems and human impacts on these systems. Systematic observations of organisms and processes from an early age can help children develop ecological knowledge and skills, and deepen their connection to the natural world. Yet recent educational reforms may privilege other scientific and engineering practices (SEPs) over OBE methods. We used lexical analysis of Next Generation Science Standards documents to identify instances of observational methods suggested in the SEPs and ecology‐related performance expectations (PEs). We identify where observations are included and omitted in these documents. Only 16 of the 175 (9%) learning progression descriptions for the SEPs explicitly mention observations. Nine out of 142 (6%) PEs related to ecology require observations. OBE opportunities were particularly scarce in middle and high school years, and missing entirely from PEs for disciplinary core ideas related to ecosystems and human impacts on ecosystems. We consider how these missed opportunities may constrain place‐based learning in natural environments, and reflect on implications for educators, students, and nonhuman others.